The impact of blockchain adoption on supply chain financing and E-commerce platform dynamics - Shangyu Pi (PLoS ONE, 2026)
The integration of blockchain technology is reshaping e-commerce supply chains and creating new dynamics for financially constrained firms. This study investigates the operational and financial implications of blockchain adoption within a supply chain consisting of a financially constrained manufacturer and a dominant e-commerce platform. Our analysis spans three common entry modes—self-operated, Fulfillment by Platform (FBP), and Sales on Platform (SOP)—and considers two key financing schemes: bank financing and equity financing. Using a game-theoretic framework, we find that while blockchain generally enhances profitability, its strategic value is highly contingent upon the chosen entry mode. Specifically, the self-operated mode grants the platform greater flexibility in pricing and service, whereas the FBP and SOP modes lead to more stable operational decisions. Our analysis further reveals a critical interplay between financing and operations: platforms maximize their gains by pairing the self-operated mode with equity financing, while a manufacturer’s optimal financing strategy shifts from bank to equity as production costs rise. These findings offer actionable insights for managers on leveraging blockchain to optimize financing choices and enhance competitive advantage. This study is, however, limited by certain simplifying assumptions, including linear demand and a uniform consumer response to blockchain, and its scope is restricted to bank and equity financing.